Pengaruh Akun Instagram @Quranreview dalam Meningkatkan Pemahaman Ayat Al-Qur’an pada Mahasiswa UINSU - Hafiz, Alfin Qodri; Nurbahri, Andini (Universitas Prof. Dr. Moestopo (Beragama), 2023)
This research aims to explore the impact of the Instagram account @Quranreview on enhancing the understanding of Quranic verses among students at the State Islamic University of North Sumatra (UINSU). The data analysis method used is a quantitative approach, with data collected through the distribution of questionnaires to students at the UINSU who use Instagram. Sample selection involves purposive sampling, with 100 respondents participating. Subsequently, the data is processed using the statistical software SPSS version 23. The research findings reveal a T-value of 3.833, which is greater than the T-table value of 1.984, indicating a significant relationship between the variable of the Instagram account @Quranreview and the understanding of Quranic verses among UINSU students. Thus, it can be concluded that the use of social media, especially Instagram, has a positive impact on religious understanding. This research holds important implications for maximizing educational strategies by leveraging social media to enrich religious education in higher education settings.